Arkansas travelers : geographies of exploration and perception, 1804-1834 - Milson, Andrew J. (Arkansas history (Fayetteville, Ark.), 2019)
""I reckon stranger you have not been used much to traveling in the woods." This remark from a hunter to Henry Rowe Schoolcraft as he trekked through the Ozark backcountry in late 1818 is one of many entertaining and eye-opening encounters between Arkansas travelers and settlers depicted in this book. Arkansas Travelers: Geographies of Exploration and Perception, 1804-1834, is the first book to capture the fascinating stories of William Dunbar, Thomas Nuttall, Henry Rowe Schoolcraft, and George William Featherstonhaugh between two covers. These four travelers explored Arkansas during a transformative period between the Louisiana Purchase of 1803 and statehood in 1836. Historian and geographer Andrew J. Milson takes readers on an enthralling tour with these travelers as they faced treacherous rivers, drunken scoundrels, and repulsive food. But Milson also cautions that the dramatic imagery, provocative epithets, and frightful anecdotes common in travel narratives too often result in distorted geographical understandings of a place. Milson explains how the language in each of these travelers' published narratives reveals perceptions of places and landscapes that can be mapped. When mapped, travelers' perceptions reveal not just what the traveler said, but where he said it. The resulting maps of these four travelers' perceptions of Arkansas illustrate the places experienced and perceived rather than simply the spaces they traversed. This geographical focus on the history of these spaces yields a deeper understanding - a deeper map - of the Arkansas past"--